2008
DOI: 10.1097/acm.0b013e3181637edc
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Preparedness: Addressing a Residency Training Gap

Abstract: As the importance of physician involvement and leadership in crisis preparedness is recognized, the literature suggests that few physicians are adequately trained to practice effectively in a large-scale crisis situation. A logical method for addressing the emergency preparedness training deficiency identified across several medical specialties is to include disaster and emergency preparedness training in residency curricula. In this article, the authors outline the development and implementation of an emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
1
27
0
2
Order By: Relevance
“…Besides, their knowledge, attitude and behavior about health emergencies and the response capacity are directly related to the control and prevention of public health emergencies. However, research have indicated that primary care medical staffs of many countries are not ready to deal with the public health emergencies [8,9,14,15], which mainly due to the lack of training and experience about public health emergencies [16-18]. The public health emergencies are usually sudden, unpredictable and with considerable severity.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, their knowledge, attitude and behavior about health emergencies and the response capacity are directly related to the control and prevention of public health emergencies. However, research have indicated that primary care medical staffs of many countries are not ready to deal with the public health emergencies [8,9,14,15], which mainly due to the lack of training and experience about public health emergencies [16-18]. The public health emergencies are usually sudden, unpredictable and with considerable severity.…”
Section: Discussionmentioning
confidence: 99%
“…Effective response to a major incident and the quality of outcomes for the hospital requires adequate skills in hospital personnel, and also organizational preparedness (6). Evidence, however, from both research and real-life events, shows that health systems and hospitals in developed countries are poorly prepared to deal with major incidents (7)(8)(9)(10). In addition, staff are not familiar with the major incident plans or confident of their role in an incident (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Among the few specific findings about key factors in successful training, an exercise involving 17 local health district risk communicators in Georgia, U.S.A., found that participants had much greater difficulty following risk communication principles under the time pressures of a realistic and stressful simulation than they did in a tabletop exercise. Participants did report highly enhanced awareness, readiness, and knowledge after the real-time simulation Ablah, et al, 2007;Dausey et al, 2006;Leaming, et al, 2013;Sandstrom et al, 2014;Uddin et al, 2008; forgetting to include expression of empathy and using too much bureaucratic speech; media talking points not shared with hospitals and other agencies; participants not adequately monitoring media developments; notification lists often used indiscriminately and not usable by back-ups in their current format; departments waiting until they were contacted to start communicating with the public, meaning they often responded defensively and had trouble quickly formulating an initial message that was clear, informative, and alleviated anxiety. In South Africa, hospital preparedness for risk communication and public relations was found to be among the lowest preparedness of areas assessed.…”
Section: F O R P E E R R E V I E W O N L Ymentioning
confidence: 99%
“…(Modified BMJ) Low Uddin, et al, 2008 Formalized competency-based all-hazards curriculum. Purpose: to assess student perception of curriculum in U.S.A.…”
Section: F O R P E E R R E V I E W O N L Ymentioning
confidence: 99%